2019
DOI: 10.1210/jc.2018-02411
|View full text |Cite
|
Sign up to set email alerts
|

Positive Impact of Genetic Test on the Management and Outcome of Patients With Paraganglioma and/or Pheochromocytoma

Abstract: Context Pheochromocytomas and paragangliomas (PPGLs) are characterized by a strong genetic component, with up to 40% of patients carrying a germline mutation in a PPGL susceptibility gene. International guidelines recommend that genetic screening be proposed to all patients with PPGL. Objective Our objective was to evaluate how a positive genetic test impacts the management and outcome of patients with SDHx or VHL-related PPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 26 publications
2
55
0
6
Order By: Relevance
“…Screenings advices do not only differ between the different mutations, but also over time, because studies on penetrance differ over time regarding the population studied (index included or not), the imaging methods used and the duration of follow‐up. Adherence to screening, leads to the detection of smaller PCC/PGL and might even lead to an improved survival for patients who develop metastases, although this is based on only few patients …”
Section: Phenotype Of Sdhx Mutation Carriersmentioning
confidence: 99%
“…Screenings advices do not only differ between the different mutations, but also over time, because studies on penetrance differ over time regarding the population studied (index included or not), the imaging methods used and the duration of follow‐up. Adherence to screening, leads to the detection of smaller PCC/PGL and might even lead to an improved survival for patients who develop metastases, although this is based on only few patients …”
Section: Phenotype Of Sdhx Mutation Carriersmentioning
confidence: 99%
“…In addition, PGL/PCC have the highest rate of germline susceptibility, which is at almost 40% [10][11][12]. Thus genetic testing, combined with clinical manifestations, biochemical, and imaging assessments, can help to understand tumor secretion, tumor malignancy, and develop treatment and follow-up plans for PPGL [12,13]. For this missed diagnosis, tests for hormones and their metabolites or genetics were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…Positive benefits of early genotyping in a P-PGL cohort was demonstrated by a French study. A set of 221 patients with P-PGL with SDHB, SDHC, SDHD, or VHL germline mutations revealed that patients who knew their genetic mutation within one year of initial P-PGL diagnosis compared to patients knowing their genetic mutation more than a year after initial diagnosis had improved follow-up (more frequent examinations, less patients lost to follow-up), smaller size of subsequent new P-PGLs discovered, lower metastatic spread, and improved 5 year survival rate in the patients who developed metachronous metastases [43]. Germline and somatic mutations in more than 20 genes (EPAS1,…”
Section: Geneticsmentioning
confidence: 99%